A role for Arabidopsis growth-regulating factors 1 and 3 in growth-stress antagonism - Piya, Sarbottam (Journal of experimental botany, 2020)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.